Sistem Informasi Penjualan Rumah Secara Kredit - Ajeng Hidayati; Muhammad Kharis Akbar (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2020)
In the current era of globalization, information technology is moving very fast. Computers, which are equipment created to facilitate human work. The rapid development of technology requires companies to develop themselves so that they can remain competitive. Home sales is one of the companies that also needs technology assistance to make transactions easier. Moreover, selling houses on credit. Companies need a supporting information system for the company. For this reason, research on the home sales information system on credit was carried out. Currently there are many companies engaged in property. The existing system in the company still uses a manual system so that it can result in high operational costs and also inefficient time used. Therefore, the existing manual system in the company can be changed to be computerized. So that the use of a reliable computerized system can solve existing problems, and with a reliable computerized system, an effective and efficient activity can be achieved in supporting the activities of the company.